The Effects of Diaphragmatic Breathing Exercises on Individuals with Premature Ejaculation: A Randomized Controlled Trial - Erkut, Umit; Karagözoğlu Coşkunsu, Dilber; Erkut, Kubra; Özden, Ali Veysel; Coskunsu, Dilber Karagozoglu (Oxford University Press, 2025)
Background There are no standardized, evidence-based rehabilitation protocols for premature ejaculation (PE) which hinders effective management, the development of validated patient-reported outcomes, regulatory oversight, and the potential benefits of targeted interventions. Aim To investigate the effect of diaphragmatic breathing exercises (DBE) on PE. Methods Sixty-two participants with PE were randomly assigned to Group I (n = 31) or Group II (n = 31). Both groups received behavioral therapy (BT) and pelvic floor muscle training (PFMT) twice daily, three days a week, for eight weeks. Additionally, Group I recieved DBE twice daily, every day, for eight weeks. Intravaginal ejaculation latency time (IELT) was calculated with a stopwatch, at the end of the 8th week (post-treatment), and at 1-year follow-up. Pelvic floor muscle (PFM) strength and endurance were evaluated with ultrasound, and changes in the in the autonomic nerves system (ANS) parameters (including the root mean square of successive differences [RMSSD], proportion of NN50 [PNN50], low-frequency [LF] power, and high-frequency [HF] power) were evaluated with an Elite HRV device at pre-treatment and post-treatment by a blinded assessor. Outcomes Primary outcome measurements were IELT, PFM strength and endurance, and changes in ANS paramaters. Results The study was completed by 29 participants (mean age = 31.4 ± 6.5 years) in Group I and 30 (mean age = 31.3 ± 7.6 years) in Group II. At post-treatment, all outcome measures showed significant improvements in both groups (P <.001 for all). Compared to Gropu II, Group I showed significantly greater improvements in IELT(P=0.12), RMSDD (P<.001), PNN50 (P=.003), LF Power (P<.001), HF Power (P=.003), strength(P<.001), and endurance (P<.001). The median IELT increase from baseline to post-treatment was 283 seconds (range: 84-870; 900%) in Group I and 204 seconds (range: 44- 581; 690%) in Group II. While IELT declined significantly from post-treatment to 1-year follow-up in Group II, no statistically significant change was found in Group I. Clinical Implications The effect of DBE on the ANS may help regulate the ejaculatory reflex. Strengths and Limitations This is the first study to apply breathing exercises with BT and PFMT in men with PE. Limitations include the lack of exercise adherence records beyond 8 weeks and the estimation-based IELT measurement at baseline. Conclusion Adding DBE, to BT and PFMT, yields better results in IELT (at 8 weeks and 1 year) and inreases PFM strength and endurance of PFM (at 8 weeks) in men with PE. © 2025 Elsevier B.V., All rights reserved.
Keywords: Behavioral Therapy; Diaphragmatic Breathing Exercises; Intravaginal Ejaculation Latency Time; Pelvic Floor Muscle Training; Premature Ejaculation; Elite HRV Corsense Device; G*Power; IBM SPSS Statistics for Windows Version 20.0; Sonosite M Turbo; Adult; Article; Autonomic Nervous System; Behavior Therapy; Body Mass; Breathing Exercise; Clinical Trial; Controlled Study; Digital Rectal Examination; Heart Rate Variability; Human; Major Clinical Study; Male; Patient-Reported Outcome; Pelvis Floor Muscle; Prospective Study; Randomized Controlled Trial; Root Mean Squared Error; Sexual Behavior; Sexual Intercourse; Diaphragm; Muscle Strength; Pathophysiology; Pelvic Floor; Procedures; Rehabilitation; Therapy; Treatment Outcome; Young Adult; Breathing Exercises; Humans